2020
DOI: 10.1007/jhep09(2020)129
|View full text |Cite
|
Sign up to set email alerts
|

The soft $$ \mathcal{S} $$-matrix in gravity

Abstract: The gravitational $$ \mathcal{S} $$ S -matrix defined with an infrared (IR) cutoff factorizes into hard and soft factors. The soft factor is universal and contains all the IR and collinear divergences. Here we show, in a momentum space basis, that the intricate expression for the soft factor is fully reproduced by two boundary currents, which live on the celestial sphere. The first of these is the supertranslation current, which generates spacetime supertranslations. The second is its symplectic partner, the G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 22 publications
0
115
0
Order By: Relevance
“…that has, in fact, already appeared in [84,85] for electrons and gravitons, respectively. In the next section we focus on the factorization (2.10) and we reveal the role of (2.11) in the case of celestial BDS amplitudes.…”
Section: Jhep06(2021)171mentioning
confidence: 86%
See 1 more Smart Citation
“…that has, in fact, already appeared in [84,85] for electrons and gravitons, respectively. In the next section we focus on the factorization (2.10) and we reveal the role of (2.11) in the case of celestial BDS amplitudes.…”
Section: Jhep06(2021)171mentioning
confidence: 86%
“…Another interesting aspect has been emphasized in [85] for graviton amplitudes. They have shown that there is a link between the resummation of IR divergences in graviton amplitudes and memory effects.…”
Section: Final Remarksmentioning
confidence: 99%
“…On each of these surfaces, the superrotation part of the extended algebra is given by the Witt algebra only if there are two particles/punctures. In this context, complementary aspects of the BMS group have been discussed in [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93].…”
Section: Jhep06(2021)079mentioning
confidence: 99%
“…From these considerations, it seems to us that investigating holography in AdS with a dissipative system coupling to an environment would be a excellent starting point to apprehend flat holography in d > 2. More specifically, it would be interesting to understand how the recent advances in the celestial sphere CFT description [125][126][127][128][129][130][131][132][133][134][135][136][137][138][139] are related to the AdS results through a flat limit process.…”
Section: Jhep05(2021)210 6 Commentsmentioning
confidence: 99%